2020
DOI: 10.3390/su12041612
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Patients’ Perception and Satisfaction with the Romanian Healthcare System

Abstract: Measuring patient satisfaction of healthcare service quality represents a significant element of a healthcare's system (HS) overall evaluation. It is the starting point for creating policies in national healthcare. The purpose of this paper was to evaluate Romanian patients' perception and satisfaction of the quality of the national HS as a whole and of its components. Exploratory and descriptive research was used. Data were collected through face-to-face interviews with Romanian patients, based on a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
(51 reference statements)
2
19
0
1
Order By: Relevance
“…Improving the provided services quality of the healthcare system in Romania (including increased system financing) will generate higher patients' satisfaction and implicitly their improving treatment adherence [51].…”
Section: Discussionmentioning
confidence: 99%
“…Improving the provided services quality of the healthcare system in Romania (including increased system financing) will generate higher patients' satisfaction and implicitly their improving treatment adherence [51].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of publication there were no studies in Romania investigating communication between healthcare practitioners and families of children with obesity in relation to clinical studies. However, studies investigating patient's satisfaction with the Romanian healthcare system, showed high levels of dissatisfaction, and lack of trust in medical services and healthcare professionals (32,33). Patient dissatisfaction was related to communication barriers with healthcare professionals, as well as low quality accommodation, food and hygiene in hospitals, which thus failed to provide patients with a sense of security (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies investigating patient's satisfaction with the Romanian healthcare system, showed high levels of dissatisfaction, and lack of trust in medical services and healthcare professionals (32,33). Patient dissatisfaction was related to communication barriers with healthcare professionals, as well as low quality accommodation, food and hygiene in hospitals, which thus failed to provide patients with a sense of security (32)(33)(34). Distrust toward medical services might lead to distrust toward medical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, Myburgh, Solanki, Smith, and Lalloo, (2005) stated that socioeconomic status were significant predictors of levels of satisfaction with the services of health care providers. Supported by Cosma, et al (2020) who found a statistically significant relationship between patients' satisfaction and income. Other reports revealed that lower-income respondents were more satisfied and was significantly associated with level of satisfaction (Afzal et al, 2011;Vidhya & Rajakumar, 2014;Okeke et al, 2019;Jovanovic, et al, 2020)…”
Section: Association Of Patients' Satisfaction and Socio-demographic mentioning
confidence: 96%